Avifauna Diversity in the Gate between Humid Atlas and Saharan Desert: Midelt Province, Morocco - Mansouri, Ismail; Squalli, Wafae; El Agy, Abdelbari; Ben Hichou, Badr; El Hassani, Abderahim; El Ghadraoui, Lahcen; Dakki, Mohamed (International Journal of Zoology, 2021)
The analysis of biological diversity at a regional scale is the first step to understand and classify the biological importance of a specific region and therefore the adoption of implementing conservation strategies. We conducted weekly bird counts by using the point count method from January 2015 to December 2017 in Midelt province, Morocco. A total of 130 bird species were observed, among breeding, migrant, and wintering species belonging to 42 families. Accipitridae (15 species), Muscicapidae (9 species), and Alaudidae (9 species) were the most observed families. Order of Passeriformes was the dominant order represented with 16 families and 68 species. Moreover, five species of conservation concern were recorded such as the vulnerable European turtle dove, houbara bustard, and Dupont’s lark; the near threatened ferruginous duck and bearded vulture; and the endangered Egyptian vulture. On the other hand, the results of the diversity analysis (Margalef index, Shannon–Wiener index, and Simpson index) showed the highest diversity in wetlands, forests, steppes, and farmlands, while cliff, landfills, and urban areas were the least diversified habitats. Finally, with its geographic situation between humid Atlas and Sahara desert, as well as the diversity of habitats and avifauna, Midelt region needs advanced analysis in terms of biodiversity and environmental characteristics, in order to provide effective conservation management.